Harmony of Behavior and Environment: The Role of Risks, Attitudes, Norms, Abilities, Self-regulation Models in Optimizing Sustainable Water Management - Putri, Enda Kalyana; Hasanah, Ana Uswatun (Indonesian Journal of Conservation, 2025)
Access to clean water remains a critical issue in urban-fringe areas where population growth, inadequate sanitation infrastructure, and behavioral patterns intersect. This study investigates the role of psychosocial factors based on the Risks, Attitudes, Norms, Abilities, and Self-regulation (RANAS) model in influencing household water management behavior in Kelurahan Tahunan, Umbulharjo District, Yogyakarta. Using a cross-sectional design and multistage random sampling across representative neighborhoods, data were collected from 97 households and analyzed through multiple linear regression. Results show that perceived risk (β = 0.229, p = 0.035), social norms (β = 0.229, p = 0.028), and abilities (β = 0.321, p = 0.003) significantly affect household behavior in managing clean water, while attitudes and self-regulation were not statistically significant. The findings underscore the importance of integrating behavioral interventions with structural improvements, particularly in areas with limited sanitation infrastructure. This study advocates for targeted community education, infrastructure development, and policy interventions that prioritize social norms and capacity-building to foster sustainable water practices.